The Effect of Combination of Prenatal Yoga and Self Hypnosis on Anxiety Level of Pregnant Women with Preeclampsia - Deasy Irawati; Ali Madinah Irawati; Siti Anisak (International Journal of Advanced Health Science and Technology, 2023)
Pregnancy and childbirth are natural processes, but they are not without risks. Health conditions, mental status and lifestyle can lead to complications, one of which is Preeclampsia. Pregnant women with preeclampsia have high anxiety in facing childbirth, due to the great risks that will be faced by themselves and the baby who is born. An effective way to overcome anxiety is by doing physical exercise, such as prenatal yoga and self-hypnosis. The purpose of the study was to explain the effect of the combination of prenatal yoga and self-hypnosis on the anxiety level of pregnant women with Preeclampsia. Method: Quasi-experimental research, pretest-posttest with control group design. The study population was all pregnant women with Preeclampsia who visited Anna Medika Madura Hospital as many as 40 people, the sample size was 20 people each for the treatment group and control group. Sampling with consecutive sampling. Research instruments Anxiety of each group was measured before and after the intervention, using the State-Trait Anxiety Inventory (STAI) questionnaire. Statistical analysis Wilcoxon Signed Rank Test and Mann Whitney U Test. Results: There is an effect of the combination of prenatal yoga and self-hypnosis on anxiety levels before and after treatment, (ρ: 0.000) and there is a significant difference in momentary anxiety levels between the treatment group and the control group (ρ: 0.000). Discussion: It can be concluded that Prenatal Yoga Gymnastics and Self Hypnosis are very useful in reducing anxiety experienced by pregnant women with Preeclampsia. Movement and relaxation in prenatal yoga exercises can increase the activity of the para-sympathetic nervous system and GABA. It is recommended to provide training programmes in ANC services on methods of reducing anxiety with alternative therapies Prenatal Yoga and Self Hypnosis.